HBR guide to coaching employees (Boston, Massachusetts, 2015)
As a manager in today's business world, you can't just tell your direct reports what to do: You need to help them make their own decisions, enable them to solve tough problems, and actively develop their skills on the job. In the 'HBR Guide to Coaching Employees' you'll learn how to: Create realistic but inspiring plans for growth Ask the right questions to engage your employees in the development process Give them room to grapple with problems and discover solutions Allow them to make the most of their expertise while compelling them to stretch and grow Give them feedback they'll actually apply Balance coaching with the rest of your workload Arm yourself with the advice you need to succeed on the job, from a source you trust. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.
Keywords: Nhân viên,Employees; Huấn luyện,Coaching of